Rapid synthesis: Identifying models and approaches to enhance the role of pharmacists in cancer care - Bain, T; DeMaio, P; Velez, CM; Bhuiya, AR; Alam, S; Khan, Z; El-Kadi, A; Wilson, MG (My University, 2023)
An in-depth synthesis of what is known based on the best available global research evidence (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about models and approaches to enhance the role of pharmacists in cancer care in response to a decision-maker's request.
Keywords: models; approaches; pharmacists; cancer care